1998
DOI: 10.1034/j.1600-0412.1998.770507.x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐1α, interleukin‐6 and interleukin‐8 in cervico/vaginal secretion for screening of preterm birth in twin gestation

Abstract: IL-8, but not IL-1alpha and IL-6, was associated with preterm delivery but the relationship was too weak to be of predictive value for preterm birth in twin pregnancies. IL-1alpha and IL-8, but not IL-6, were associated with bacterial vaginosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 27 publications
0
23
1
Order By: Relevance
“…Hitti et al (2001) reported that lower levels of H 2 O 2 -producing lactobacilli were associated with increased IL-6 in women in preterm labor, but IL-8 was not significantly elevated in that group. This study did not observe a significant difference in IL-8 between the BV-positive and BV-negative groups, while previous studies did (Spandorfer et al, 2001;Wennerholm et al, 1998). A possible explanation for this could be differences in the study groups: HIV-seropositives were assessed in the current study, while HIV-seronegative women undergoing in vitro fertilization or with twin-pregnancies were assessed in the other two studies.…”
Section: Introductioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Hitti et al (2001) reported that lower levels of H 2 O 2 -producing lactobacilli were associated with increased IL-6 in women in preterm labor, but IL-8 was not significantly elevated in that group. This study did not observe a significant difference in IL-8 between the BV-positive and BV-negative groups, while previous studies did (Spandorfer et al, 2001;Wennerholm et al, 1998). A possible explanation for this could be differences in the study groups: HIV-seropositives were assessed in the current study, while HIV-seronegative women undergoing in vitro fertilization or with twin-pregnancies were assessed in the other two studies.…”
Section: Introductioncontrasting
confidence: 53%
“…Measurement of IL-8 may therefore be useful as a biomarker of inflammation at mucosal sites, including the female genital tract. For example, high vaginal IL-8 concentrations were associated also with amniotic fluid infections in women with preterm labor (Hitti et al, 2001) and in women with bacterial vaginosis (Spandorfer et al, 2001;Wennerholm et al, 1998). Vaginal IL-8 increases were noted also after sexual activity, after exposure to some microbicides and during menses (Al-Harthi et al, 2001;Fichorova, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a study including 121 women with twin pregnancies sampled at 24, 26, 28, 30, 32 and 34 weeks of gestation determined that the levels of IL-1alpha and IL-6 in cervicovaginal secretion were not significantly associated with preterm birth [37].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence suggests that microbes associated with BV modulate the immune response [27,31,[33][34][35][36]. Many authors have found elevate levels of interleukin (IL)-1alpha or beta in vaginal secretions of BV-positive women compared to healthy controls [34,[37][38][39][40]. IL-1beta is a member of the IL-1 family, which includes the classical IL-1alpha (IL-1F1) and IL-1beta (IL-1F2) cytokines, IL-1 receptor antagonist (IL-1ra, or IL-1F3), IL-18 (IL-1F4), and the newly described IL-1F5-11 [41].…”
Section: Introductionmentioning
confidence: 99%
“…3,4 To prevent prematurity, the ideal course of action would be to predict which patients are at risk of premature delivery and then implement effective intervention. [5][6][7] In several studies, bacterial vaginosis has been associated with prematurity and other adverse outcomes, independent of other known risk factors. [8][9][10][11][12] While bacterial vaginosis has been associated with preterm delivery and low birth weight, randomized trials for the treatment of bacterial vaginosis during pregnancy have not always demonstrated a reduction in such outcomes.…”
Section: Introductionmentioning
confidence: 99%